GOOD PRICE MANY GOLD DEMANDS - Ari Susanto; Suwartono Suwartono; Sri Lestari (Media Mahardhika, 2020)
The uncertainty of the global economy and the corona outbreak, gold is the most sought after investment alternative. Therefore, when compared to other types of investment the value of gold is relatively more stable. In fact, the price of gold tends to continue to rise. But now the physical sales of gold are threatened to fall because people avoid crowded places. As a result, no one came to the gold shop. Internet marketing is a new form of business in marketing products or services and building communication with consumers through the internet. The use of internet marketing as a marketing communication medium is influenced by the increasing development of communication technology, especially the internet. The internet has changed the face of the world today, especially in the business world, the internet is fast becoming the most important part of people's lives. This study aims to determine the effect of social media marketing and viral marketing on gold purchasing decisions at Macan Gold Sidoarjo. This type of research is quantitative research which is the process of determining knowledge using the form of numbers in data. This research produces SPSS output that social media marketing and viral marketing have a significant positive effect on purchasing decisions, the use of appropriate the core of forming viral marketing is social media marketing. Consumers who like and are satisfied with promotions in social media marketing and taking viral marketing moments have an impact on gold purchasing decisions at Macan Gold Sidoarjo.